Service Encounter di Yayasan Nurul Hayat Surabaya - Firyal Afifah Huda; Ahmad Khairul Hakim (Journal of Islamic Management, 2021)
This study aims to describe the implementation of service encounters at the Nurul Hayat Foundation and the supporting and inhibiting factors in its application. To describe these two problems, the researcher used a qualitative approach with descriptive research type. The data collection techniques used were interviews, observation, and documentation. The results of this study indicate that the application of service encounters takes place in three stages, namely: pre-purchase, service encounter and post-purchase. In its implementation, service encounter support factors include: the use of SOPs as a basis for employees, a special team in monitoring employees on their SOPs, providing call centers, trying to solve any problems quickly, providing training for employees, providing product knowledge books to memorize, requiring customer service always friendly, strives to always be trustworthy in managing the money that has been given by consumers, guarantees consumer data, employees are able to adapt to every consumer who comes, requires cs employees to memorize the names of consumers who are interacting with employees, and have concrete evidence of the building and reviews from consumers. Meanwhile, the inhibiting factors for service encounters include: employees have odd jobs which can affect the service and one main building is inadequate in serving consumers